2022
DOI: 10.1051/0004-6361/202142436
|View full text |Cite
|
Sign up to set email alerts
|

Helium stars exploding in circumstellar material and the origin of Type Ibn supernovae

Abstract: Type Ibn supernovae (SNe) are a mysterious class of transients whose spectra exhibit persistently narrow He I lines, and whose bolometric light curves are typically fast evolving and overluminous at peak relative to standard Type Ibc SNe. We explore the interaction scenario of such Type Ibn SNe by performing radiation-hydrodynamics and radiative-transfer calculations. We find that standard-energy helium-star explosions within dense wind-like circumstellar material (CSM) can reach a peak luminosity of a few 104… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The strong narrow H emission lines defining the type-IIn SNe (Schlegel 1990) are clearly absent in SN 2021ocs. SNe Ibn show prominent narrow He emission lines and a rising blue part of the spectrum (Pastorello et al 2007), which originates from Fe emission (Dessart et al 2021(Dessart et al , 2022. Similarly this blue rise is also seen in SN 2021ocs, while strong He lines are absent except for the weak He I λ7065, and λ5876 which is blended with the Na I doublet λλ5890,5896.…”
Section: Interpretation: Csm Interaction or A Pulsar Wind Nebula?mentioning
confidence: 70%
See 2 more Smart Citations
“…The strong narrow H emission lines defining the type-IIn SNe (Schlegel 1990) are clearly absent in SN 2021ocs. SNe Ibn show prominent narrow He emission lines and a rising blue part of the spectrum (Pastorello et al 2007), which originates from Fe emission (Dessart et al 2021(Dessart et al , 2022. Similarly this blue rise is also seen in SN 2021ocs, while strong He lines are absent except for the weak He I λ7065, and λ5876 which is blended with the Na I doublet λλ5890,5896.…”
Section: Interpretation: Csm Interaction or A Pulsar Wind Nebula?mentioning
confidence: 70%
“…late-time ejecta-CSM interaction (e.g. Maeda et al 2015;Dessart et al 2022) or magnetar spin-down (e.g. Afsariardchi et al 2021).…”
Section: Early Spectrum and Light Curvementioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of the values derived for SN 2019hgp by Gal-Yam et al (2022); the type Icn SNe tend to produce more massive CSM than our models predict. Most importantly, these events likely require lower He mass fractions than ejected by our models (Dessart et al 2022), which typically have X He ∼ 0.8 and X CO ∼ 0.2.…”
Section: Comparisons To Ussne and Type Ibn/icn Snementioning
confidence: 86%
“…Many observational studies (Ho et al 2021;Xiang et al 2021) reveal the similarities in the light curves and spectra between FBOTs and the Type Ibn SNe (i.e. the explosion of hydrogen-poor stars, possibly stripped in binaries, with strong ejecta-CSM interaction; Pastorello et al 2007Pastorello et al , 2008Hosseinzadeh et al 2017;, and theoretically, Dessart, Hillier, & Kuncarayakti (2022) showed that the standard-energy explosions of helium stars within dense CSM are reminiscent of FBOTs while the low-energy explosions are more consistent with Type Ibn SNe. Some other astronomers suggest that FBOTs have mildly or sub-relativistic outflows (e.g.…”
Section: Introductionmentioning
confidence: 97%